Biomechanical effects of steroid injections used to treat pyogenic flexor tenosynovitis - Turvey, Blake R (BioMed Central, 2012)
BACKGROUND: A recent study from our laboratory has demonstrated improved range of motion in the toes of broiler chickens afflicted with pyogenic flexor tenosynovitis when treated with local antibiotic and corticosteroid injections, without surgical drainage. However, the use of corticosteroids as an adjunct treatment raised peer concern, as steroids are thought to have deleterious effects on tendon strength. The purpose of this study was to compare the tensile strength of the aforementioned steroid treated tendons, to a group of tendons administered with the current standard treatment: systemic antibiotics, surgical drainage and no corticosteroids. METHODS: Twenty-three tendons’ structural and material properties were investigated (fifteen receiving the standard treatment, eight receiving the steroid treatment). The measurements from each group were interpreted via Student’s unpaired t-test and a post-hoc power analysis. RESULTS: The steroid treated tendons did demonstrate a trend toward decreased mechanical properties when compared with the standard treatment group, but the results were not statistically significant. CONCLUSIONS: Treatment of septic tenosynovitis with local corticosteroid and local antibiotic injections resulted in better digital motion, without a significant loss of tendon strength, over a twenty-eight day recovery period.